2021
DOI: 10.1002/dvdy.442
|View full text |Cite
|
Sign up to set email alerts
|

Direct TGF‐ß signaling via alk4/5/7 pathway is involved in gut bending in sea urchin embryos

Abstract: Background Precise gastrulation is essential for formation of functional bodies in cnidarians and bilaterians. Previously, by using an alk4/5/7‐specific inhibitor, we showed that transforming growth factor‐beta (TGF‐ß)‐alk4/5/7 signaling pathway is important for correct gut bending in sea urchin embryos. However, it is still unclear where functional TGF‐ß signals are received in embryos for correct gut bending because details of the spatiotemporal expression pattern of alk4/5/7 have not been reported. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…pulcherrimus . The procedures for collecting gametes and handling embryos/larvae are entirely the same as those of model sea urchins, and previous reports showed that the methods for analyzing gene functions and mRNA/protein localization in other model sea urchins are also applicable to this species (Suzuki & Yaguchi, 2018, 2021; Yaguchi et al., 2020). For example, the phenotype of Nodal morphants in T .…”
Section: Temnopleurus Reevesii Has the Potential To Be A Sea Urchin G...mentioning
confidence: 99%
“…pulcherrimus . The procedures for collecting gametes and handling embryos/larvae are entirely the same as those of model sea urchins, and previous reports showed that the methods for analyzing gene functions and mRNA/protein localization in other model sea urchins are also applicable to this species (Suzuki & Yaguchi, 2018, 2021; Yaguchi et al., 2020). For example, the phenotype of Nodal morphants in T .…”
Section: Temnopleurus Reevesii Has the Potential To Be A Sea Urchin G...mentioning
confidence: 99%